How Couples Cope with Infertility - Donna Davis (EDIS)
“I’ve had many friends who, soon after they were married, were constantly facing questions from friends and relatives about when they were going to start having children. Many people assume this would be the next logical step. However, many couples choose not to have children, and more than four million married men and women in the U.S. have difficulty conceiving or carrying a child to birth.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, July 2012.